Imaging of Pancreatic Trauma—A Clinical Scenario-Based Approach - Hemachandran, Naren; Gamanagatti, Shivanand (Journal of Gastrointestinal and Abdominal Radiology, 2020)
Pancreatic injury, although uncommon in the setting of abdominal trauma, is associated with high morbidity and mortality. While the clinical signs are nonspecific, the imaging signs can be very subtle in the early stages leading to missed injuries that present later as complications. Contrast-enhanced computed tomography (CT) is the main workhorse and initial imaging modality in the setting of abdominal trauma, while magnetic resonance imaging (MRI) with magnetic resonance cholangiopancreatography is used as a problem-solving tool in pancreatic trauma.This article provides a review of the imaging of pancreatic trauma and has been organized into common clinical scenarios–Suspected pancreatic injury with normal-appearing pancreas on CT; definite pancreatic injury on CT, late presentation or complication in a patient with pancreatic injury. The role of the radiologist in each scenario is described as follows: to identify subtle secondary signs of injury and resort to MRI or a repeat imaging wherever necessary in a suspected pancreatic injury with normal-appearing pancreas on CT (Scenario 1); to look for primary/hard signs, grade the injury according to American Association of Surgery for Trauma Organ Injury Scale, and utilize MRI if necessary to ascertain the presence of ductal injury when a definite pancreatic injury is seen on CT (Scenario 2); and to diagnose various complications and help in the management of complications such as draining collections or vascular complications like pseudoaneurysms (Scenario 3).Radiologists should be aware of the primary and secondary signs of pancreatic injury so as to enable prompt diagnosis and further management. Radiologists play an important role not only in the diagnosis of pancreatic injuries but also in the management of certain complications.
Keywords: pancreatic trauma; computed tomography; MRCP; complications; angiography; CT-guided drainage